X-ray speckle reduction using a high-speed piezoelectric deformable mirror system - Shuai Yan; Hui Jiang; Zhisen Jiang; Dongxu Liang; Jianan Xie; Hai Zhu; Guoyang Shu; Ningyu Ben; Aiguo Li (High Power Laser Science and Engineering)
An advanced deformable Kirkpatrick–Baez (K-B) mirror system was developed, equipped with high-speed piezoelectric actuators, and designed to induce beam decoherence and significantly enhance the quality of X-ray imaging by minimizing undesirable speckles in synchrotron radiation or free-electron laser facilities. Each individual mirror is engineered with 36 independent piezoelectric actuators that operate in a randomized manner, orchestrating the mirror surface to oscillate at a high frequency up to 100 kHz. Through in situ imaging single-slit diffraction measurement, it has been demonstrated that this high-frequency-vibration mirror system is pivotal in disrupting the coherent nature, thereby diminishing speckle formation. The impact of the K-B mirror system is profound, with the capability to reduce the image contrast to as low as 0.04, signifying a substantial reduction in speckle visibility. Moreover, the coherence of the X-ray beam is significantly lowered from an initial value exceeding 80% to 13%.